Diabetes Insipidus due to Metastases of Undiagnosed Lung Cancer: A Case Report from Syria - Ibrahim Alali; Alaa Al-Sarraj; Younes Kabalan (Case Reports in Endocrinology)
Pituitary metastases (PM) are extremely uncommon, accounting for less than 1% of all intracranial metastases. PM of an undiagnosed malignancy can commonly present with symptoms of hormonal deficiencies, central diabetes insipidus, and/or visual symptoms. Lung and breast malignancies are the most common cancers associated with PM. Despite advances in diagnostic and therapeutic options, the prognosis remains poor and is influenced by primary malignancy and treatment methods. We report a case of a patient with PM from lung cancer who had polyuria, polydipsia, and nonspecific symptoms. A full evaluation confirmed central diabetes insipidus, hypogonadism, and metastatic lung cancer. We also discuss the current literature on PM diagnosis and management, emphasizing the need for a comprehensive evaluation of all available data. This is the first case of PM reported from Syria, to our knowledge.